2015
DOI: 10.1128/aac.02015-15
|View full text |Cite
|
Sign up to set email alerts
|

Reduced In Vitro Activity of Ceftaroline by Etest among Clonal Complex 239 Methicillin-Resistant Staphylococcus aureus Clinical Strains from Australia

Abstract: bA total of 421 methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates were tested for ceftaroline susceptibility by Etest (bioMérieux). A multidrug resistant phenotype was found in 40.9%, and clonal complex 239 (CC239) was found in 33.5%. Ceftaroline nonsusceptibility (MIC, >1.0 g/ml) was 16.9% overall. Nonsusceptibility was significantly higher in CC239 (41.1%, 58/141) and in isolates with a multidrug resistant phenotype (35.5%, 61/172) compared with comparators (P < 0.0001). Nonsusceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…AWARE data from 7 countries in the Asia-Pacific region and Australia state that 78.8% and 83.1%, respectively, of MRSA isolates collected in 2012 tested susceptible to ceftaroline. 30,31 Although resistance rates may appear low in the United States, it is important to recognize and monitor regional differences in resistance trends.…”
Section: Ceftarolinementioning
confidence: 99%
See 1 more Smart Citation
“…AWARE data from 7 countries in the Asia-Pacific region and Australia state that 78.8% and 83.1%, respectively, of MRSA isolates collected in 2012 tested susceptible to ceftaroline. 30,31 Although resistance rates may appear low in the United States, it is important to recognize and monitor regional differences in resistance trends.…”
Section: Ceftarolinementioning
confidence: 99%
“…51 It is also unclear whether ceftaroline will retain durable activity against MRSA with more frequent use because recent reports from Australia and Asia suggest higher rates of resistance than previously reported. 30,31 To date, follow-up data regarding patient outcomes from these case series have not yet been published. Results from a completed cohort study evaluating the safety and efficacy of ceftaroline in those with SAB or persistent MRSAB are expected and may provide more evidence for the use of ceftaroline for these indications.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…Dosage adjustment is required in renal impairment, specifically for patients with an estimated creatinine clearance at 50 mL/min or less [32]. Dose adjustments are made by reducing the dose instead of the dosing interval, as the efficacy of ceftaroline is mainly determined by free-drug concentration above MIC [36]. The commonest adverse drug events are diarrhea, nausea, and rash, with vomiting, headache, hypokalaemia, increased liver transaminases, and phlebitis also documented (2–3% among patients from four phase III clinical trials) [37].…”
Section: Novel Anti-gram-positive Antibioticsmentioning
confidence: 99%
“…An emerging concern with ceftaroline use is the reported decreased susceptibility and increased resistance in certain MRSA clinical isolates collected around the world [36,41,42,43]; especially high regional resistance percentages have been reported from China, Thailand, and Australia [36,43]. In particular, the in vitro study that evaluated MRSA isolates from Melbourne, Australia found significant ceftaroline resistance among MDR phenotype and the CC239 strain making it a non-ideal option for empiric treatment in suspected or known MRSA infections in regions where strain CC239 represents a significant proportion of MRSA [36]. It should be noted however, that most resistance strains have been re-categorized as intermediate with the updated The European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints [44].…”
Section: Novel Anti-gram-positive Antibioticsmentioning
confidence: 99%
“…Ceftaroline has an enhanced affinity for penicillin binding protein 2a (PBP2a), thus is an ideal antibiotic choice for MRSA infections. This antibiotic is relatively new, and was approved for use in 2010 in the U.S, 2012 in Europe, and 2013 in Australia [36]. However, the emergence of ceftaroline resistance in different parts of the world with a demonstrated decrease of PBP2a binding affinity and heteroresistance, has been documented [37][38][39].…”
Section: Ceftarolinementioning
confidence: 99%